ADRB2 Gene Polymorphism and Physical Activity with Energy Balance in Obesity Patients - Hafizth, Hendi; Sulastri, Delmi; Amir, Arni (Sarana Ilmu Indonesia (Salnesia), 2025)
Obesity is recognized as a major global health problem due to its negative impact on quality of life and its strong association with various metabolic disorders. Energy imbalance, defined as a condition in which energy intake consistently exceeds energy expenditure, is considered a central mechanism in the development of obesity. This study aimed to examine the relationship between physical activity, ADRB2 gene polymorphism zygosity (rs1042713), and energy balance among individuals with obesity. A quantitative cross-sectional design was implemented, involving 48 obese participants selected using a total sampling technique. Data were obtained through structured interviews, anthropometric measurements, and genetic testing. Statistical analyses were conducted using the Chi-square test, Fisher’s exact test, and logistic regression analysis. The results indicated a statistically significant association between physical activity and energy balance status (p-value = 0,003). No significant association was identified between ADRB2 gene zygosity and energy balance (p-value = 1,000). The findings highlight the important role of physical activity in preventing excess energy accumulation among obese individuals, while the genetic variation examined did not show a significant contribution in this study. Limitations include the cross-sectional design, which precludes causal inference, and the relatively small sample size, which limits the generalizability of the results. Promotion of an active lifestyle remains a fundamental strategy in adult obesity management.